Hajj to the Heart : Sufi Journeys across the Indian Ocean - Kugle, Scott Alan, 1969- (Book collections on Project MUSE., 2021)
"Against the sweeping backdrop of South Asian history, this is a story of journeys taken by sixteenth-century reformist Muslim scholars and Sufi mystics from India to Arabia. At the center is the influential Sufi scholar Shaykh ʻAli Muttaqi and his little-known network of disciples. Scott Kugle relates how ʻAli Muttaqi, an expert in Arabic, scriptural hermeneutics, and hadith, left his native South Asia and traversed treacherous seas to make the Hajj to Mecca. Settling in Mecca, he continued to influence his homeland from overseas. Kugle draws on his original translations of Arabic and Persian manuscripts, never before available in English, to trace ʻAli Muttaqi's devotional writings, revealing how the Hajj transformed his spiritual life and political loyalties. The story expands across three generations of peripatetic Sufi masters in the Mutaqqi lineage as they travel for purposes of pilgrimage, scholarship, and sometimes simply for survival along Indian Ocean maritime routes linking global Muslim communities. Exploring the political intrigue, scholarly debates, and diverse social milieus that shaped the colorful personalities of his Sufi subjects, Kugle argues for the importance of Indian Sufi thought in the study of hadith and of ethics in Islam"--